Integrative functional genomics identifies an enhancer looping to the SOX9 gene disrupted by the 17q24.3 prostate cancer risk locus - Zhang, Xiaoyang; Cowper-Sal·lari, Richard; Bailey, Swneke D.; Moore, Jason H.; Lupien, Mathieu

(untitled) (Genome Research, 2012)
Genome-wide association studies (GWAS) are identifying genetic predisposition to various diseases. The 17q24.3 locus harbors the single nucleotide polymorphism (SNP) rs1859962 that is statistically associated with prostate cancer (PCa). It defines a 130-kb linkage disequilibrium (LD) block that lies in an ∼2-Mb gene desert area. The functional biology driving the risk associated with this LD block is unknown. Here, we integrate genome-wide chromatin landscape data sets, namely, epigenomes and chromatin openness from diverse cell types. This identifies a PCa-specific enhancer within the rs1859962 risk LD block that establishes a 1-Mb chromatin loop with the SOX9 gene. The rs8072254 and rs1859961 SNPs mapping to this enhancer impose allele-specific gene expression. The variant allele of rs8072254 facilitates androgen receptor (AR) binding driving increased enhancer activity. The variant allele of rs1859961 decreases FOXA1 binding while increasing AP-1 binding. The latter is key to imposing allele-specific gene expression. The rs8072254 variant in strong LD with the rs1859962 risk SNP can account for the risk associated with this locus, while rs1859961 is a rare variant less likely to contribute to the risk associated with this LD block. Together, our results demonstrate that multiple genetic variants mapping to a unique enhancer looping to the SOX9 oncogene can account for the risk associated with the PCa 17q24.3 locus. Allele-specific recruitment of the transcription factors androgen receptor (AR) and activating protein-1 (AP-1) account for the increased enhancer activity ascribed to this PCa-risk LD block. This further supports the notion that an integrative genomics approach can identify the functional biology disrupted by genetic risk variants.